"You don't immediately stick a label on them": a qualitative study of influences on general practitioners' recording of anxiety disorders. Issue 6 (23rd June 2016) - Ford, Elizabeth; Campion, Alice; Chamles, Darleen Aixora; Habash-Bailey, Haniah; Cooper, Maxwell
Abstract : Objectives: Anxiety is a common condition usually managed in general practice (GP) in the UK. GP patient records can be used for epidemiological studies of anxiety as well as clinical audit and service planning. However, it is not clear how general practitioners (GPs) conceptualise, diagnose and document anxiety in these records. We sought to understand these factors through an interview study with GPs. Setting: UK National Health Service (NHS) General Practice (England and Wales). Participants: 17 UK GPs. Primary and secondary outcome measures: Semistructured interviews used vignettes to explore the process of diagnosing anxiety in primary care and investigate influences on recording. Interviews were transcribed verbatim and analysed using thematic analysis. Results: GPs chose 12 different codes for recording anxiety in the 2 vignettes, and reported that history, symptoms and management would be recorded in free text. GPs reported on 4 themes representing influences on recording of anxiety: 'anxiety or a normal response', 'granularity of diagnosis', 'giving patients a label' and 'time as a tool'; and 3 themes about recording in general: 'justifying the choice of code', 'usefulness of coding' and 'practice-specific pressures'. GPs reported using only a regular selection of codes in patient records to help standardise records within the practice and as a time-saving measure. Conclusions: We have identified a coding culture where GPs feel confident recognising anxiety symptoms; however, due to clinical uncertainty, a long-term perspective and a focus on management, they are reluctant to code firm diagnoses in the initial stages. Researchers using GP patient records should be aware that GPs may prefer free text, symptom codes and other general codes rather than firm diagnostic codes for anxiety.